The organization of dialogue interaction in small learning groups (Pedagogy of Higher and Secondary Education, 2013)
Krivshenko L. M. The organization of dialogue interaction in small learning groupsThe article reveals the experience of organization of primary school learners’ dialogue activity in small groups, the attention is paid to the most frequently used interactive forms and methods of teaching.
Keywords: dialogue interaction; interaction; interactive methods; small learning group; communicative skills; mutual learning